+0  
 
+4
351
1
avatar+8 

a) |a + b| ≥ ||a| − |b||,

 

b) |a + b| ≤ |a + b| + |a − b|.

 17.04.2016
 #1
avatar+200 
0

Hallo beshoo293,

zu a):

Die Gleichung ist symmetrisch, da \(|a-b|=|b-a|\)

Wir setzen also: \(a\geq b\)

 

Fall 1: \(a\geq b\geq 0\)

Wir erhalten \(a+b\geq a-b~~~~~\rightarrow gilt.\)

 

Fall 2: \(a\geq 0>b\)

Wir erhalten \(||a|-|b||\geq ||a|-|b|| ~~~~~~\rightarrow gilt.\)

 

Fall 3: \(0>a\geq b\)

\(-a-b\ge |-a-b| ~~~~~\rightarrow gilt. \)

 

zu b):

\(|a-b|\ge 0\) (laut Def.)

Also auch: \(|a + b| ≤ |a + b| + |a − b| \)

 

 

Grüße

melwei

 18.04.2016

5 Benutzer online

avatar
avatar